A note on estimation via linearly combining two given staistics - Jürgen Groß (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 1997)
Linear combination of two statistics is considered when some prior knowledge about their expectation and complete knowledge about their joint dispersion is available. The considered setup is more general than those already known in the literature, in the sense that the expectation of one of the statistics is not necessarily assumed to be completely known when estimation of the expectation of the other statistic is of interest.
Keywords: 519; Linear combination of statistics; Gauss-Markov model; minimum dispersion linear unbiased estimation; covariance adjustment estimation; prediction